Analisis Sikap Kerja Mahasiswa Tata Boga FT UNP dalam Pelaksanaan Praktek Lapangan Industri (PLI) di Berbagai Hotel Kota Padang - Mairoza, Dini; Silfeni, Silfeni; Chair, Ira Meirina (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The aim of this research is to describe the attitude of the PKK’s Tata Boga FT UNP students in PLI from the discipline and the careness. This research is the qualitative descriptive research with ex post facto approach. This research is done in some hotels in Padang such as Basko Premier Hotel, Pangeran Beach Hotel, HayamWuruk Hotel and Rocky Plaza Hotel. The data collection through interview with 10 informants who are the kitchen and pastry supervisor. The data validation is done by triangulation method. The result shows that (1) the students of Tata Boga UNP generally have the good attitude during PLI in some hotels in Padang, (2) the students have the good discipline to their jobs and the role of the industry, only some of them who break the rule, such as their absence during PLI, (3) the students have the good careness to their jobs, their environment, and only some of them still don’t aware of the safety. Keywords :Discipline, Caraness